Response of Gut Microbiota to Dietary Fiber and Metabolic Interaction With SCFAs in Piglets - Liu, Boshuai; Wang, Wenjing; Zhu, Xiaoyan; Sun, Xiao; Xiao, Junnan; Li, Defeng; Cui, Yalei; Wang, Chengzhang; Shi, Yinghua (Frontiers in Microbiology, 2018)
Dietary fiber (DF) is increasingly thought to regulate diversity of piglet gut microbiota to alleviate weaning stress in piglets. This study was conducted to investigate the effects of DF on growth performance of piglets and composition of their gut microbiota, as well as the interaction between gut microbiota and short-chain fatty acids (SCFAs) in piglets. A total of 840 piglets were allocated to three dietary treatments consisting of a control group (CG), an alfalfa meal group (AG), and a commodity concentrated fiber group (OG) in a 30-day feeding trial. Gut mucosa and feces samples were used to determine bacterial community diversity by 16S rRNA gene amplicon sequencing. Fiber treatment had a positive effect on growth performance and metabolism of SCFAs in piglets, in particular, compared with CG, the diarrhea rate was significantly decreased, and the content of propionic acid in the cecum was markedly increased in AG. The Shannon indices of the jejunum microbiota in AG were higher than CG. At the genus level, compared to CG, in the duodenum, the relative abundance of Paenibacillus in AG and OG was higher; in the jejunum, the relative abundances of Bacillus, Oceanobacillus, Paenibacillus, Lactococcus, Enterococcus and Exiguobacterium were higher, whereas the relative abundance of Mycoplasma was lower in AG; in the cecum, there was also lower relative abundance of Helicobacter in AG and OG, and furthermore, the relative abundance of Faecalibacterium in OG was higher than in CG and AG. Spearman correlation analysis showed that Pseudobutyrivibrio was positively correlated with acetic acid, propionic acid and butyric acid, while Bacteroides and Anaerotruncus were negatively correlated with propionic acid and butyric acid. In addition, microbiota analyses among different intestine segments showed distinct differences in microbiota between the proximal and distal intestines. Bacteria in the proximal segments were mainly Firmicutes ,while bacteria in the distal segments were mainly Bacteroidetes and Firmicutes. Overall, these findings suggested that DF treatment could reduce the diarrhea rate of piglets and had beneficial effects on gut health, which might be attributed to the alteration in gut microbiota induced by DF and the interaction of the gut microbiota with SCFAs.